Imagination, cognitive tools and reluctant students (Praxis Educativa, 2012)
This paper analyzes how children and teenagers whom we call “reluctant students” are often, anything but reluctant to learn some things. They show all kinds of signs of imaginative participation- but their participation seems unable to connect with the school syllabus. We could wonder: How could we manage to have a curriculum so imaginative and attractive as the world that is exposed to the students? A new answer for some or a lot of those students could come from Lev Vygotsky’s research (1962, 1997). His notion of “cognitive tools” gives us a way to explore how we could capture and involve those students’ imagination to make them see that, what is really wonderful and engaging in the syllabus, could be learnt by anyone and could be turned into a cognitive tool. In this paper we shall see how the cognitive tools to make up stories, the binary opposites and the images generated through words, could be used in a new way. Each of them was at one point, a considerable important cultural invention, and each of them turns now, into a potential cognitive tool to increase our ability to think, communicate and understand.
Keywords: imagination; curricular contents; cognitive tools